A Defleksi Vertikal Poros Turbin Angin Multi Blade di Daerah Pedesaan Bagian III: Kaji Teoritik dan Numerik - Koten, Viktus; Leda, Jeremias Mathias (Jurnal Teknik Mesin Indonesia, 2025)
The multi-blade wind turbine is a type of wind turbine that has been used by salt farmers in Paccelang Village, Bangkala District, Jeneponto Regency, South Sulawesi Province. In operation, the turbine often experiences resonance due to excessive vertical deflection of the shaft. This article examines and identifies the parameters that cause vertical shaft deflection. Research was carried out theoretically and numerically. Theoretically, the research was carried out by entering the appropriate parameters into the described shaft vertical deflection equation. Numerically, research was carried out using autodesk inventor software. The parameters that cause excessive vertical deflection of the shaft and are sorted based on their contribution are reduction in shaft diameter, extension of the shaft, and increase in external load